Aiming for Health Equity: The role of Public Health Policy and Primary Healthcare; Comment on "Universal Health Coverage for Non-Communicable Diseases and Health Equity: Lessons From Australian Primary Healthcare" - Bo Burström (Kerman University of Medical Sciences, 2022)
This commentary refers to the article by Fisher et al on lessons from Australian primary healthcare (PHC), which highlights the role of PHC to reduce non-communicable diseases (NCDs) and promote health equity. This commentary discusses important elements and features when aiming for health equity, including going beyond the healthcare system and focusing on the social determinants of health in public health policies, in PHC and in the healthcare system as a whole, to reduce NCDs. A wider biopsychosocial view on health is needed, recognizing the importance of social determinants of health, and inequalities in health. Public funding and universal access to care are important prerequisites, but regulation is needed to ensure equitable access in practice. An example of a PHC reform in Sweden indicates that introducing market solutions in a publicly funded PHC system may not benefit those with greater needs and may reduce the impact of PHC on population health.